The effect of early deprivation on executive attention in middle childhood. (24th August 2012) - Loman, Michelle M.; Johnson, Anna E.; Westerlund, Alissa; Pollak, Seth D.; Nelson, Charles A.; Gunnar, Megan R.
Abstract : Background: Children reared in deprived environments, such as institutions for the care of orphaned or abandoned children, are at increased risk for attention and behavior regulation difficulties. This study examined the neurobehavioral correlates of executive attention in post institutionalized (PI) children. Methods: The performance and event‐related potentials (ERPs) of 10‐ and 11‐year‐old internationally adopted PI children on two executive attention tasks, Go/No‐go and Flanker, were compared with two groups: children internationally adopted early from foster care (PF) and nonadopted children (NA). Results: Behavioral measures suggested problems with sustained attention, with PIs performing more poorly on Go trials and not on No‐go trials of the Go/No‐go and made more errors on both congruent and incongruent trials on the Flanker. ERPs suggested differences in inhibitory control and error monitoring, as PIs had smaller N2 amplitude on Go/No‐go and smaller error‐related negativity on Flanker. Conclusions: This pattern of results raises questions regarding the nature of attention difficulties for PI children. The behavioral errors are not specific to executive attention and instead likely reflect difficulties in overall sustained attention. The ERP results are consistent with neural activity related to deficits in inhibitory control (N2) and error monitoring (error‐related negativity). Questions emerge regarding the similarity of attention regulatory difficulties in PIs to those experienced by non‐PI children with ADHD.